2017
DOI: 10.1038/srep40683
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive optical estimate of tissue composition to differentiate malignant from benign breast lesions: A pilot study

Abstract: Several techniques are being investigated as a complement to screening mammography, to reduce its false-positive rate, but results are still insufficient to draw conclusions. This initial study explores time domain diffuse optical imaging as an adjunct method to classify non-invasively malignant vs benign breast lesions. We estimated differences in tissue composition (oxy- and deoxyhemoglobin, lipid, water, collagen) and absorption properties between lesion and average healthy tissue in the same breast applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 54 publications
2
67
0
1
Order By: Relevance
“…The absorption coefficient at 976 nm reflected the relative amount of water in the phantom, whereas the absorption coefficient at 936 nm did not necessarily reflect the relative amount of lipid in the phantom. Taroni et al used seven wavelengths from 635 to 1060 nm to measure collagen as an important biomarker in a pathological classification [32]. They stated that 635 and 1060 nm were very effective wavelengths for collagen identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption coefficient at 976 nm reflected the relative amount of water in the phantom, whereas the absorption coefficient at 936 nm did not necessarily reflect the relative amount of lipid in the phantom. Taroni et al used seven wavelengths from 635 to 1060 nm to measure collagen as an important biomarker in a pathological classification [32]. They stated that 635 and 1060 nm were very effective wavelengths for collagen identification.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the presence or absence of collagen affects the calculation of other parameters [33]. The level of collagen varies with age, body mass index (BMI), and breast density [17,34], and is reported to be involved in tumor development and progression [32]. It is difficult to measure collagen with the wavelengths of 760-1000 nm used in this study, as the absorption of collagen is lower than that of water and lipid at those wavelengths, and the spectral peak positions of lipid and collagen are similar within this wavelength range [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a 12-channel TD-NIRS system for optical mammography with a hand-held probe shown in Figure 11b was developed to be used at a bed side [53]. Another TD-NIRS system for optical mammography, as shown in Figure 11c, was developed by a group from Italy to obtain TR transmittance images of compressed breasts [54]. The results of these systems are briefly described later in Sections 5.2.1 and 5.3.5.…”
Section: Td-dot and Td-nirs Systems For Optical Mammographymentioning
confidence: 99%
“…Photos of (a) the 48-channel TD-DOT for optical mammography [52]; (b) the 12-channel TD-NIRS system for optical mammography with a hand-held probe [53], and (c) the transmittance Figure 11. Photos of (a) the 48-channel TD-DOT for optical mammography [52]; (b) the 12-channel TD-NIRS system for optical mammography with a hand-held probe [53], and (c) the transmittance TD-NIRS imaging system for optical mammography with breast compression [54]. (b) Reproduced from Reference [53].…”
Section: Td-dot and Td-nirs Systems For Optical Mammographymentioning
confidence: 99%
See 1 more Smart Citation